Pelatihan Relaksasi Nafas Dalam untuk Mengatasi Tekanan dari Potensi Bahaya Psikososial pada Pekerja Informal: Deep Breath Relaxation Training to Cope with Stresses from Potential Psychosocial Hazards in Informal Workers - Merijanti, Lie Tanu; Pusparini, Pusparini; Mediana, Dian; Prasetyadi, Indiarto Nindyo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Informal workers have faced higher pressure in meeting performance demands, especially amidst financial stability that has not been constant. Sometimes there isn't even a clear line between personal life and work life. After the pandemic there has been a shift in workers from the formal sector to the informal sector, where the number of informal workers has increased by 15.6%, while the formal sector has contracted - 6%. Informal sector workers are dominated by self-employed activities with limited capital and low levels of education, wading through life in the capital. Jakarta is included in the top ten ranking as a city with a high level of stress, where one of the parameters for the assessment is based on reports of workers experiencing stress. Therefore it is necessary to provide education and training to overcome potential psychosocial hazards through deep breathing relaxation techniques. The activity was carried out in December 2022 in collaboration with the Indonesian Buddhist Clinic partners by inviting 22 informal sector workers who often interact with partners, around the location where the partners are located. The activity began with pre-testing, providing material as well as training, debriefing, and closing with filling in the post-test. From the results of the pre and post test assessments, it was found that there was an increase in knowledge and understanding of 63.6% related to the material presented.